Make Constitutionalism great again? Sobre la necesidad de provincializar el constitucionalismo.: Make Constitutionalism great again? On the need to provincialize Constitutionalism - Winter Pereira, Luisa (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
This paper tackles the question of how constitutionalism, which will be called modern/colonial, maintains a strategy of conquest and expropriation of constitutional knowledge from the global south. To put forward this idea, it will turn to the work of four major constitutionalists from the global north: Grimm, Zagrebelsky, Garrorena and Fioravanti. It will study how they shape the modern/colonial constitutional canon, including the operation of silencing other constitutional realities. The final aim of the paper is to provide theoretical tools to articulate the possibility of provincializing constitutionalism.